Evaluation of the discrepancy of the bolton ratio in three groups of sagittal skeletal relationships - Mostafa Ahmadi; Mohammad Chehrazi; Reza Ghorbanipour (Babol University of Medical Sciences, 2023)
Introduction: The outcome of orthodontic treatment depends on the malocclusion and the ratio of the size of the upper and lower teeth. The aim of this study was to evaluate the discrepancy of tooth crown size in different groups of malocclusions. Materials & Methods: In this cross-sectional study, 165 patients referred to the Orthodontic Department of Babol School of Dentistry were randomly selected. The samples were divided into three skeletal malocclusion groups (55 in each group) according to the ANB angle. The level of anterior and total Bolton ratio in the cases was calculated, and the deviation from normal value of anterior and posterior Bolton was calculated. The results were analyzed using the ANOVA and chi-square test. The significance level was set at p <0.05. Results: The sample consists of 80 males and 85 females aged 12 to 25 years. The mean and standard deviation of the anterior tooth ratio were 79.06 ± 2.87 in Cl I, 79.23 ± 3.18 in Cl II, and 80.16 ± 3.71 in Cl III, and there was no significant difference between the mean anterior ratio between the malocclusion groups. The mean and standard deviation of the total Bolton ratio (TBI) were 91.3 ± 2.39 in Cl I, 91.6 ± 2.49 in Cl II, and 92.49 ± 2.64 in Cl III and the difference between the mean total ratio among the groups was statistically significant. Conclusion: Based on the results of this study between different groups of malocclusion, clinicians should consider the detailed examination of dental proportions in the diagnosis and treatment planning stage.